Problems and Prospects of Vegetables Gardening In Machchhegaun: A Case Study - Paudyal, Narayan Prasad (Tribhuvan University Journal, 2016)
Agriculture production contributes 32.60 percent of GDP in which vegetable contribution is 9.7 percent in Nepalese economy. This article triesto find out the conditions and state of vegetable production and productivity, including problems and prospects of Machchhegaun, one of the villages of ward no. 7 of Kirtipur Municipality. This village is good for vegetable production due to suitable climate, good topography, fertile land and market accessibility. Of the total arable land, only 6.9 percent is for vegetable production. However, its yield is higher as compared to other staple food crops like paddy, maize and wheat. This apparently shows that there is higher potentiality of vegetable gardening which can be helpful to fulfill the requirements of vegetables to the growing population of Kirtipur Municipality. However the farmers are facing many problems like that of lacking technical knowledge, lack of improved seeds, fertilizer, agriculture equipments and financials supports.